2022
DOI: 10.3390/app12178728
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Chrysin in Improving Bone Health

Abstract: Vitamin D deficiency is endemic worldwide. Although several strategies have been established to enhance vitamin D3 levels, studies specifically focusing on the inhibition of vitamin D metabolism, which may prolong the availability of active vitamin D in pathological conditions, have been less explored. Studies also suggest that higher doses of vitamin D3 fail to achieve optimum vitamin D levels. In this context, we focused on the enzyme CYP3A4, which promotes the inactivation of active vitamin D. The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…It was observed that the liquid state SLNs were stable for 90 days and the freeze-dried SLNs were stable up to 1 year [27]. These studies indicate that SLNs are suitable for herbal medicine delivery [28,29].…”
Section: Ultrasonicationmentioning
confidence: 77%
“…It was observed that the liquid state SLNs were stable for 90 days and the freeze-dried SLNs were stable up to 1 year [27]. These studies indicate that SLNs are suitable for herbal medicine delivery [28,29].…”
Section: Ultrasonicationmentioning
confidence: 77%
“…In Kasarla et al's study, the impact of chrysin, a proven inhibitor of the CYP3A4 enzyme, which promotes the inactivation of active vitamin D, as an intervention, as well as its effects when used in combination with low-dose vitamin D3 (40 IU) to maintain bone health in conditions of vitamin D deficiency, was evaluated. The results obtained indicate that although chrysin alone had a notable effect on 25-hydroxyvitamin D3 and bone tissue, it had an intensified therapeutic effect when used in combination with vitamin D3 and CaCO3 to improve bone health [24].…”
mentioning
confidence: 91%